Classroom learning styles and the effects they have on foreign language learners - Ibañez Salazar, Roberto; Vásquez De León, José Amadeo (2024)
THIS bibliographical argumentative essay describes, analyses, and argues the most relevant learning styles in the learning process. The learning styles (see gloss for definition) are qualities that human beings possess. These are characterized or classified as the potential capacities that every learner has. These learning styles determine the way students develop their abilities in terms that these learners reflect a faster or a slower learning. Also, these styles allow students to have success and achieve their goals through their own learning pattern. Firstly, it is good to have in mind that in every learning process, there are internal and external factors, and also aspects that are essential in the students’ learning process. In addition, these learners have a variety of abilities that are combined all together. These abilities will permit the students to accomplish their goals. In this manner, we can say that every student has different ways of learning because they are different from one to another. It is the reason that we have concentrated on learning styles’ details and those components that deal with them. Learning styles play on learners a valuable innate ability. For this significant reason, we have delimited the topic on “Classroom Learning Styles and the Effects They Have on Foreign Language Learners”. In this sense, if learning styles are developed appropriately and efficiently, they will create success on students. Besides, the teachers must encourage the learners to work on their own learning styles; also, teachers should implement or apply activities in which students must develop their abilities. In addition, teachers should help students to guide themselves and create a well deve-lopmental process. Hence, as we know, the learning styles are different in every student. For this reason, it is good to know how these styles work in each foreign language-learning student. Moreover, the importance to know how deep the relation is between the students learning styles and the way they learn. Besides that, by identifying the role that these learning styles play on foreign language learners, we can discover some other factors that are closely connected with these styles. Also, it is good to know how these learners are characterized by these factors or categories such as personality factors, learning patterns, and multiple intelligences. We know that this argumentative essay will help students to find out the styles they have. In this manner, the learners will find themselves capable of learning better and efficiently. By knowing the innate styles the students have, they will have a wider view in how to learn a foreign or second language. If the students work out their learning styles appropriately, it is for sure that these will have success in any particular foreign language learning.